EDUKASI KEADAAN MENTAL ANAK USIA DINI SEBAGAI PENCEGAHAN INSECURE DENGAN MENGUBAH PERSPEKTIF SEORANG ANAK - Weda, Chintiya; Robi'ah, Dewi; Eka Zeni Safitri; Firnanda, Shella Hadi Ayu; Marselli, Rina; Ayu, Meilany Kusuma; Rahayu, Puji (FKIP Unirow Tuban, 2024)
The issue that drives this research is that a lot of parents underestimate their children's mental health in favor of their physical health, a problem that has existed for a long time. In response, scientists carried out studies meant to arm parents with information on how to preserve and comprehend their child's physical and emotional well-being. Researchers will organize research materials pertaining to early childhood experiences of insecurity, read and take notes, and gather library data through the literature study approach.